Crimes contra as relações de consumo: uma teoria a partir da jurisprudência - Bosch, Marcia Helena (2016)
This work, which bends on the subject of the crimes against consumer relations, through an analysis of the jurisprudence related to crimes inserted in the Consumer Protection Code (CDC) and that of the Article 7, IX, of Law 8137/90 (which have as good legally protected the consumer relation) aims to strengthen the defined thesis that the crimes specified in the CDC does not have effectiveness in the political environment , social , economic and legal Brazilians, however paradoxical it may be, because we live in a consumer society (over-indebtedness) even after twenty-four years of validity of this law. With the methodological support of the bibliographic research and examination of judgments delivered in superior courts and in eight state courts, the effort concentrates (i) in the study of the construction of consumers rights faced to his vulnerability in a dynamic and innovative mass market, (ii) the crimes defined by the legislator, that using originality elected to consumer relations as well to be protected by the state, anchored in principles, and in the general theory of criminal law that supports it, (iii) in effecting the criminal protection in jurisprudential seating extracted of selected cases. Regarding to the crime of the Article 7, IX, of Law 8.137/90 (sell, have on deposit, expose for sale or delivery of raw materials or goods unfit for consumption), based on the examined cases, it is apparent that the recognition of the crime has been systematically denied inasmuch as, through misinterpretation of the crime theory, and even faced with the dimension of new rights (third generation rights), it is required for the configuration of these crimes, effective harm to legally protected good (production of naturalistic results), despising up the doctrinal classification of this crime, which is crime of danger (presumed)